Living like there’s no tomorrow: Saving and spending following the Sichuan earthquake - Filipski, Mateusz J.; Jin, Ling; Zhang, Xiaobo; Chen, Kevin Z. (International Food Policy Research Institute, 2015)
In addition to human casualties and physical damage to infrastructure, natural disasters affect survivors emotionally and psychologically. Research on such impacts has almost exclusively been confined to the medical field, and focused on severe conditions such as post-traumatic stress disorder. The fact that emotional shocks and increased risk awareness may trigger changes in the preferences and behavior of economic agents has until now largely been ignored, including by economists. Based on panel datasets from China’s Sichuan province, which was struck by an earthquake in 2008, and using distance from epicenter as a proxy for earthquake severity, we empirically show that the saving and consumption behavior of households closer to the epicenter changed after the earthquake. They saved less, spent more lavishly on alcohol and cigarettes, and also played majiang (a Chinese game) more often. The magnitude of the estimated impact on saving behavior, a drop of 6 percentage points for each degree of earthquake intensity, is economically significant. It appears that the earthquake has induced a shift in people’s preferences characterized by a carpe diem attitude toward spending and greater preference for the present.